African Development Indicators 2004 : Drawn from the World Bank Africa Database - World Bank (Africa Development Indicators, 2004)
African Development Indicators 2004 provides the most detailed collection of data on Africa available in one volume. It contains more than 500 macroeconomic, sectoral, and social indicators, covering 53 African countries with data from 1970-2002. The book is grouped into 15 chapters: background data; national accounts; prices and exchange rates; money and banking; external sector; external debt and related flows; government finance; agriculture; power, communications, and transportation; public enterprises; labor force and employment; aid flows; social indicators; environmental indicators; and HIPC debt initiative. Each chapter begins with a brief introduction on the nature of the data and their limitations, followed by a set of statistical tables, charts, and technical notes that define the indicators and identify their specific source. Included this year are new tables on HIV/AIDS, Communications and Transportation, and the HIPC Debt Initiative. Designed to provide all those interested in Africa with a focused and convenient set of data to monitor development programs and aid flows in the region, this is an invaluable reference tools for analysts and policymakers who want a better understanding of the economic and social developments occurring in Africa